2006
DOI: 10.1128/aem.01374-06
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Biodetoxification of S, N, and O Pollutants by Engineering of a Carbazole-Degrading Gene Cassette in a Recombinant Biocatalyst

Abstract: The gene cassette encoding enzymes responsible for degrading carbazole to anthranilic acid was introduced into a dibenzothiophene degrader. The resultant strain, Rhodococcus erythropolis XPDN, could simultaneously transform the model pollutants dibenzothiophene, carbazole, and dibenzofuran to nontoxic metabolites and may have an application potential for bioremediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Bioremediation is a potential treatment alternative for eliminating these contaminants in the environment. Fundamental research has been conducted to examine the biodegradation of these hazardous compounds (Fedorak & Grbić-Galić, 1991;Boyd et al, 1993;Kropp et al, 1994a;Boyd et al, 2003;Yu et al, 2006;Safinowski et al, 2006;Gai et al, 2007;Wang et al, 2007). However, it remains unclear whether benzothiophenes have an inhibitory effect on N-heterocyclic compounds such as CA, although other studies have shown that S-, N-and O-heterocyclic aromatic compounds can have a significant inhibitory effect on the biodegradation of polycyclic aromatic hydrocarbons (Dyreborg et al, 1996a(Dyreborg et al, , b, 1997Meyer & Steinhart, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Bioremediation is a potential treatment alternative for eliminating these contaminants in the environment. Fundamental research has been conducted to examine the biodegradation of these hazardous compounds (Fedorak & Grbić-Galić, 1991;Boyd et al, 1993;Kropp et al, 1994a;Boyd et al, 2003;Yu et al, 2006;Safinowski et al, 2006;Gai et al, 2007;Wang et al, 2007). However, it remains unclear whether benzothiophenes have an inhibitory effect on N-heterocyclic compounds such as CA, although other studies have shown that S-, N-and O-heterocyclic aromatic compounds can have a significant inhibitory effect on the biodegradation of polycyclic aromatic hydrocarbons (Dyreborg et al, 1996a(Dyreborg et al, , b, 1997Meyer & Steinhart, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has also isolated and constructed several bacteria that can degrade these heterocyclic compounds (6,18,19,20,43,44). The isolates degrade carbazole by following similar pathways, in which carbazole is initially attacked at the angular position by dioxygenation, followed by spontaneous conversion of the dihydroxylated intermediate to 2Ј-aminobiphenyl-2,3-diol.…”
mentioning
confidence: 99%
“…R. erythropolis XP is a strain isolated from soils and has been proved efficient in deep desulfurization of petroleum oils, including gasoline, diesel, and crude oil, through the 4S pathway (10,12). Strain XP was also successfully used as a host for developing a recombinant biocatalyst for biodetoxification of S/N/O pollutants (11). Therefore, strain XP was considered to be potentially one of the best strains for use in industrial desulfurization (5).…”
mentioning
confidence: 99%